2014
DOI: 10.1111/1749-4877.12016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of larval size and hydrodynamics on the growth rates of the black fly Simulium tribulatum

Abstract: Black flies are ubiquitous and important members of lotic ecosystems. Size is known to affect many aspects of their life in the aquatic larval stage, including intraspecific competition for feeding sites. As filter feeders, flow affects their ability to feed and reach sufficiently fast flow. This, in turn, can lead to risky fluid-mediated dispersal behavior in search of better conditions. It is surprising, therefore, that little information is available regarding how physiological and environmental factors com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This aligns with our study findings, underscoring the critical role of altitude in a suitable environment for S. qinghaiense. Previous studies have indicated that the abundance of blackflies is higher and the young larvae exhibit faster growth rates in fastflowing streams [69,70]. It is worth noting the influence of current velocity on S. qinghaiense.…”
Section: Discussionmentioning
confidence: 90%
“…This aligns with our study findings, underscoring the critical role of altitude in a suitable environment for S. qinghaiense. Previous studies have indicated that the abundance of blackflies is higher and the young larvae exhibit faster growth rates in fastflowing streams [69,70]. It is worth noting the influence of current velocity on S. qinghaiense.…”
Section: Discussionmentioning
confidence: 90%
“…We used water velocity as a measure of resource availability because of its demonstrated strong influence on the feeding performance of Simulium tribulatum, one of the most widespread and well-studied blackflies in North America. Rates of ingestion and growth of larval blackflies increase with increasing velocity (Charpentier & Morin, 1994;Finelli et al, 2002;Brannin, O'Donnell & Fingerut, 2012), often leading to greater male mating success and female fecundity (Tarrant et al, 1983;Edman & Simmons, 1985). Moreover, while near-bed velocities experienced by benthic biota can exhibit marked spatial variation within individual substrates as well as among different habitat types (e.g.…”
Section: Introductionmentioning
confidence: 99%